Carbon dioxide mass transfer within algal raceway ponds and the potential for improvement using slopes to create wave - Burke, Matthew (Centre for Bioprocess Engineering Research, 2016)
The growth of microalgae has the potential to be extremely useful for the production of a wide range of products or for specific processes, such as capture and cycling of CO₂. The fast micro-algal growth rates and ability to grow on agriculturally poor land and in waste water means that bio-production using algae has many advantages over traditional agricultural processes for certain applications. The raceway pond is the most common reactor used for the growth of microalgae, due to low capital costs, low operating costs, higher energy efficiency, improved net energy recovery and ease of installation. Low carbon dioxide mass transfer, which limits algal growth and productivity, is currently one of the largest issues in photo bioreactors of all forms. The microalgae within these systems only obtain carbon from the dissolved inorganic carbon and hence sufficient carbon dioxide mass transfer is one of the most important design parameters for any photobioreactor. This is particularly evident in raceway ponds as they have a lower volumetric mass transfer rate than other photobioreactors and are typically mass transfer limited. [Please note: the full text of this thesis has been deferred until 30 September 2017]